Bioprospecção de óleos essenciais de especiarias e avaliação das atividades antioxidante, tóxica e antibacteriana contra Corynebacterium diphtheriae - ALVES, Marcia Barros (2023)
Diphtheria is a bacterial disease caused by Corynebacterium diphtheriae, which has worrying reports of resistance to the drugs of choice. In this context, the growing interest in use of essential oil (EO) can be an aid in primary health care. In this work, the objective was to investigate chemical compositions of EOs of the popular spices Cinnamomum verum J. Presl. (cinnamon) and Syzygium aromaticum (L.) Merr. & L.M. Perry (clove) and biological activities on isolates of C. diphtheriae. The plant inputs of C. verum (leaves) and S. aromaticum (inflorescences) were subjected to EO extraction, through water vapor drag, which were subjected to chemical analysis by gas chromatography coupled to mass spectrometry. Subsequently, the antioxidant capacity was analyzed using the ammonium phosphomolybdenum method. Hemolytic activity was also verified and bioassays were carried out on Artemia salina and Tenebrio molitor with the EOs. Experiments were also carried out to determine the minimum inhibitory and bactericidal concentration of EOs in 5 clinical samples of C. diphtheriae isolated in Maranhão and 2 standard samples. As it presented a minimum inhibitory concentration for all isolates, the influence of EO of S. aromaticum on bacterial morphology and biofilm formation was examined at a concentration ½ of the inhibitory concentration. The majority compound for both EOs was eugenol, with 72.11% in that of C. verum and 44.29% in that of S. aromaticum. The EO of C. verum showed 21.5% antioxidant activity and that of S. aromaticum 40.6%. The hemolytic activity of EOs was considered low, with EO of C. verum causing hemolysis at a concentration of 225 µg/mL and S. aromaticum at a concentration of 514 µg/mL. In the toxicity assessment for A. salina, the EO of C. verum presented an LC50 of 1.37 µg/mL and the S. aromaticum LC50 of 377.25 µg/mL, demonstrating high toxicity. In tests with T. molitor, the average survival rate was 56.88% with the application of EO of C. verum and 80% with EO of S. aromaticum. Four of the isolates had growth inhibited by EO of C. verum at concentrations ranging between 1,500 and 750 μg/mL, however, for none of these, a minimum bactericidal concentration was observed, while all isolates were inhibited at concentrations ranging between 1,000 and 62.5 µg/mL with the EO of S. aromaticum and for two of the tested isolates there was a minimum bactericidal concentration of 2,000µg/mL. The EO of S. aromaticum was not able to alter bacterial morphology and for only one isolate it inhibited biofilm production. Thus, the EOs demonstrated the capacity to inhibit the tested isolates and, in their composition, substances with antimicrobial activities already described in the literature, whose properties may indicate interesting characteristics for the production of new drugs.